1984
DOI: 10.1128/iai.43.3.804-810.1984
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression in Escherichia coli of the streptolysin O determinant from Streptococcus pyogenes: characterization of the cloned streptolysin O determinant and demonstration of the absence of substantial homology with determinants of other thiol-activated toxins

Abstract: A gene bank of Streptococcus pyogenes Richards was constructed in Escherichia coli by using the bacteriophage replacement vector lambda L47.1, and hybrid phage expressing streptolysin O (SLO) were identified among the recombinants. DNA sequences encoding SLO were subcloned from an slo+ hybrid phage into a low-copy-number vector plasmid to yield an slo+ hybrid plasmid, pMK157. This plasmid contains 5.6 kilobase pairs of cloned streptococcal DNA sequences, is stable, and expresses SLO at easily detectable levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…The 4.5-kb XbaI fragment hybridized with the pGAC106 probe and was therefore cloned into the pACYC184 plasmid using SalI and XbaI. The pACYC184 vector was chosen to bypass potential stability problems of this group A streptococcal insert in E. coli, as was reported by Kehoe and Timmis (34). Antibiotic sensitivity and DNA hybridization indicated that one recombinant plasmid, pGAC112, contained the proper insert.…”
Section: Resultsmentioning
confidence: 99%
“…The 4.5-kb XbaI fragment hybridized with the pGAC106 probe and was therefore cloned into the pACYC184 plasmid using SalI and XbaI. The pACYC184 vector was chosen to bypass potential stability problems of this group A streptococcal insert in E. coli, as was reported by Kehoe and Timmis (34). Antibiotic sensitivity and DNA hybridization indicated that one recombinant plasmid, pGAC112, contained the proper insert.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the deletions observed is not clear, but may be due to some instability of streptococcal DNA in E co//(e.g. see Kehoe and Timmis, 1984). High-level expression of the p antigen was only observed after thermo-induction with clone pPGJI (see Fig.…”
Section: Identification Of Two Regions Coding For Iga-binding Activitymentioning
confidence: 91%
“…At that time, the chromosomal sequence of NZ131 had not been determined so gene Spy49_ 1180 was temporarily labeled as the Ex sequence, and gene Spy49_ 0145 was combined into the whole slo upstream sequence (17). The promoter-less ermB gene is silent because it is preceded by the chimerical Spy49_ 0145 -Spy49_ 1180 sequence in which a weak slo promoter found inside the Spy49_ 0145 gene (19, 20) is inactive due to the proximity of the Spy49_ 1180 sequence (17, 20). The insertion, selected by resistance to tetracycline, occurred via recombination between the plasmid and chromosomal Spy49_ 1180 sequences resulting in the strain OK173 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1c). Since all experiments were performed in vitro (THY medium), the possibility remains that some unknown physiological factor might activate the transposed promoter or the previously identified weak slo promoter (19, 20) when synthesis of slo gene but not the nga gene is required.…”
Section: Discussionmentioning
confidence: 99%